Onset of exchange flow in combined buoyancy and forced pipe flow in unstable density gradient. (January 2016) - Maeda, A.; Yamagata, T.; Fujisawa, N.
Abstract: The onset of exchange flow and the flow structure in a combined buoyancy and forced pipe flow are experimentally studied at Reynolds number up to 7000. The experiment is carried out in a vertical pipe flow of water issuing into a still brine water environment of various concentrations and flow rates. The critical Froude number for the onset of exchange flow is evaluated by the laser-induced fluorescence technique and the velocity fields near the pipe exit are measured by the particle-image velocimetry. The critical Froude number in the laminar regime increases with increasing the Reynolds number and the onset of inflow and the purging of the exchange flow are deviated due to the hysteresis effect, while it is not observed in the turbulent regime. It is found that the laminar exchange flow is characterized by the large-scale structure and the turbulent exchange flow is featured by the small-scale structure near the wall. The enhancement of velocity fluctuation near the pipe exit is clearly observed in the laminar regime due to the occurrence of exchange flow, while it is limited to the near-wall region in the turbulent regime.